Targeting KIFC1 Promotes Senescence in Soft Tissue Sarcoma via FXR1‐Dependent Regulation of MAD2L1 mRNA Stability - Xiu‐Xia Lu; Yi Que; Jing Yang; Li‐Yuan Le; Qi‐Yan Cai; Bu‐Shu Xu; Dong‐Chun Hong; Yao Liang; Xing Zhang (Advanced Science)
Abstract Patients diagnosed with soft tissue sarcoma (STS) often present at intermediate to advanced stages, with inherently limited therapeutic options available. There is an urgent need to identify novel therapeutic targets. In this study, by screening STS data from the Cancer Genome Atlas (TCGA) and Genotype Tissue Expression (GTEx) databases, KIFC1 is identified as a potential biomarker and a promising therapeutic target for STS. Notably, a significant increase in KIFC1 levels, which exhibited a strong correlation with a poor prognosis in STS patients is observed. The findings revealed that knockout of KIFC1 suppressed STS growth both in vitro and in vivo. Furthermore, KIFC1 is found to regulate cellular senescence in STS, which has not been reported before. that targeting KIFC1 induced cellular senescence via interacting with FXR1, an RNA‐binding protein is discovered, thereby further stabilizing MAD2L1 mRNA in an m6A‐dependent manner. Additionally, the suppression of KIFC1 markedly diminished the growth of patient‐derived xenografts (PDX) and triggered senescence. This study provides the first evidence that KIFC1 inhibition induces cellular senescence through MAD2L1, underscoring KIFC1 as a novel prognostic biomarker and a potential therapeutic target for STS.